Technology capability and E-Commerce adoption in SMEs: How does geographical location play a role? - Salmizi, Aisyah Nurain; Abd Aziz, Nurul Nadia; Abu Yazid, Zaidatul Nadiah; Samsudin, Mawarti Ashik; Abd Majid, Azeman (Journal of Islamic, Social, Economics and Development, 2025)
This study explores the nexus between technological capability and e-commerce adoption among SME entrepreneurs alongside the potential influence of geographic location on such relationship. A questionnaire was distributed to 260 SMEs (150 rural and 110 urban) within the state of Selangor, Malaysia. The results showed that geographic location had no moderating effect on the relationship between technology capabilities and e-commerce adoption. This suggests that the geographical location factor will become less important if there are efforts to enhance technological capability in promoting the adoption of e-commerce among SMEs. Future research can expand this study by focusing on other developed and under-developed states in Malaysia.